Bioavailability, Pharmacokinetics, and Safety of Belimumab Administered Subcutaneously in Healthy Subjects. Issue 4 (26th August 2013) - Cai, Wendy W.; Fiscella, Michele; Chen, Cecil; Zhong, Z. John; Freimuth, William W.; Subich, David C.
Abstract This Phase 1 study evaluated the absolute bioavailability, pharmacokinetics (PK), tolerability, and safety of belimumab 200 mg/mL administered subcutaneously (SC) to healthy subjects as a single dose and as multiple doses up to 240 mg. In all, 118 subjects (age range 18–55 years; body weight 51–115 kg) were enrolled. Seventy‐eight subjects received a single dose of belimumab 240 mg intravenously, or 2 × 120, 1 × 240, or 1 × 200 mg SC. Forty subjects received 4 weekly injections of belimumab 2 × 120 or 1 × 200 mg SC. Randomization was stratified by weight (<75 kg vs. ≥75 kg) and injection site (abdomen vs. thigh). Following single belimumab SC doses, bioavailability was 74–82%, indicating that belimumab SC was well absorbed, and bioavailability was similar among the three SC groups. Following 4 weekly belimumab SC doses, bioavailability was similar to that following single SC administration. Four subjects had persistent positive immune responses; neutralizing antibodies in these subjects were not detected and there was no apparent impact on PK. Belimumab was generally well tolerated after single and multiple SC dosing, and 200 mg SC weekly dosing is expected to provide an exposure similar to 10 mg/kg intravenously every 28 days.